Potential Antimicrobial Properties of Coffee Beans and Coffee By-Products Against Drug-Resistant Vibrio cholerae - Rawangkan, Anchalee; Siriphap, Achiraya; Yosboonruang, Atchariya; Kiddee, Anong; Pook-In, Grissana; Saokaew, Surasak; Sutheinkul, Orasa; Duangjai, Acharaporn (Frontiers in Nutrition, 2022)
Vibrio cholerae is the causative organism of the cholera epidemic, and it remains a serious global health problem, particularly the multidrug-resistant strain, despite the development of several generic drugs and vaccines over time. Natural products have long been exploited for the treatment of various diseases, and this study aimed to evaluate the in vitro antibacterial activity of coffee beans and coffee by-products against V. cholerae antimicrobial resistant strains. A total of 9 aqueous extracts were investigated, including light coffee (LC), medium coffee (MC), dark coffee (DC), dried green coffee (DGC), dried red coffee (DRC), fresh red coffee (FRC), Arabica leaf (AL), Robusta leaf (RL), and coffee pulp (CP). The influential coffee phytochemicals, i.e., chlorogenic acid (CGA), caffeic acid (CA), and caffeine, were determined using HPLC. The antibacterial properties were tested by agar well diffusion techniques, and the MIC and MBC were further determined against 20 V. cholerae isolates. The results revealed that all tested strains were sensitive to coffee extracts, with MIC and MBC values in the range of 3.125–25.0 mg/mL and 12.5–50.0 mg/mL, respectively. With a MIC of 6.25 mg/mL, DGC, DRC, and CP appeared to be the most effective compounds against 65%, 60%, and 55% of clinical strains, respectively. The checkerboard assay revealed that the combination of coffee extract and tetracycline was greater than either treatment alone, with the fractional inhibitory concentration index (FICI) ranging from 0.005 to 0.258. It is important to note that CP had the lowest FICI (0.005) when combined with tetracycline at 60 ng/mL, which is the most effective dose against V. cholerae six-drug resistance strains (azithromycin, colistin, nalidixic acid, sulfamethoxazole, tetracycline, and trimethoprim), with a MIC of 47.5 µg/mL (MIC alone = 12.5 mg/mL). Time killing kinetics analysis suggested that caffeic acid might be the most effective treatment for drug-resistant V. cholerae as it reduced bacterial growth by 3 log10 CFU/mL at a concentration of 8 mg/mL within 1 h, via disrupting membrane permeability, as confirmed by scanning electron microscopy. This is the first report showing that coffee beans and coffee by-product extracts are an alternative for multidrug-resistant V. cholerae treatment.